Demethylation of Cancer/Testis Antigens and CpG ODN Stimulation Enhance Dendritic Cell and Cytotoxic T Lymphocyte Function in a Mouse Mammary Model. (4th November 2013) - Sun, Jun-Zhong; Gao, Lei; Gao, Li; Wang, Wei; Du, Nan; Yang, Juan; Wan, Ling; Liu, Fang; Wang, Li-li; Yu, Li
Abstract : Background . Cancer/testis antigens (CTAs) are ideal targets for cancer immunotherapy in virtue of their restricted expression profile in normal tissues. However, CTA-targeted immunotherapy has been rather disappointing clinical setting for CTAs are downregulated by cytosine-phosphate-guanosine (CpG) methylation in their promoter regions, so that tumor cells have low immunogenicity. Methods . We reinduced mouse CTA P1A through demethylation process and generated P1A-specific cytotoxic lymphocytes (CTLs) by immunizing BALB/c (H-2 d ) mice with dendritic cells pulsed with a P1A-specific peptide and CpG oligodeoxynucleotide (ODN) immune adjuvant. Results . We found that demethylation and CpG ODN immune adjuvant stimulation facilitated DC maturation and enhanced the allogenic capacity of P1A-specific CTLs against target cells both in vitro and in vivo . Conclusions . Our results suggested that CTA induction and immune adjuvant stimulation is a feasible strategy in cancer immunotherapy.